IMPLEMENTATION OF DAILY SERVICES FOR JEMBER POPULATION ADMINISTRATION LAHBAKO (Daily Service for the Jember Population Administration) IN AMBULU DISTRICT - Itok Wicaksono Wicaksono; Maulida Rahmatul Ilmi (POLITICO, 2022)
Public services are present as a form of service and government performance as a regulator in running and managing the ongoing government. The form of public services is divided into various forms and each has its own target as an effort to enforce the government process and control the administration.The community as the recipient of public services is also the party who is obliged to not only receive services, but also to implement and comply with the rules set by the government as a government regulator.The form of public service itself is dynamic enough to adapt to the conditions and needs that develop in the community. The online population administration process and program as implemented by Dispendukcapil Jember in the Lahbako application network is one example of the implementation of public services in the population administration sector which has experienced adjustments and changes due to several factors that occur in the community itself. Ambulu sub-district is a quite interesting locus, apart from heterogeneity but also various other factors that make the implementation of the LAHBAKO application network in the sub-district has a different and interesting value.Keywords: Implementation, population administration, LAHBAKO